2013
DOI: 10.37285/ijpsn.2012.5.4.9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and In vivo Characterization of Pectin Based In situ Gelling System of Famotidine

Abstract: In this study famotidine was used as a model drug to formulate and evaluate pH-induced in situ gelling system for oral sustained release drug delivery in stomach which has shorter biological half-life. To study the effect of independent variables 32 full factorial design was employed, concentration of pectin as pH dependant polymer and concentration of calcium chloride on dependent variables like viscosity, drug content, 50% and 80% drug release and similarity factor. It was found that both the concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Based on the study, it was observed that formulation with HPMC shown satisfactory floating behaviors. 36,37 and it is shown in Tables 3 and 4.…”
Section: In Vitro Floating Studies Of Carvedilol Floating In Situ Gelmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the study, it was observed that formulation with HPMC shown satisfactory floating behaviors. 36,37 and it is shown in Tables 3 and 4.…”
Section: In Vitro Floating Studies Of Carvedilol Floating In Situ Gelmentioning
confidence: 99%
“…Gelling capacity was graded based on the gelation time and time for which formed gel retained. 36,37 + Gelation after few minutes dispersed rapidly ++ Gelation immediate remains for few hours +++ Gelation immediate remains for an extended period…”
Section: In Vitro Gelationmentioning
confidence: 99%
“…Bench top digital pH meter was calibrated with standard buffer solutions of pH 4, 7 and 10 before the determination of the pH of trial gel formulations. Dispersions of trials were prepared by adding 1gm of gel content in 100mL of deionized water (Modasiya, Prajapati et al, 2015). The pH of the trials was noted in triplicate.…”
Section: Ph Determinationmentioning
confidence: 99%
“…The molecular weight and solubility of XNT are 218.33 g/ mol and 28.90 μg/ml, respectively. This makes XNT have lower molecular weight and higher solubility compared with bioactive compound curcumin [60,61]. Thus, it was expected that XNT might easily penetrate the surface of biofilm.…”
Section: Xanthorrhiza Roxb Extraction Preparationmentioning
confidence: 99%